PERANG BHARATA (BHARATAYUDDHA) DI ERA REFORMASI - I Ketut Agus Murdiana; I Made Arsa Wiguna (Guna Widya: Jurnal Pendidikan Hindu, 2020)
War Of Bharatayuddha is a story that tells about the war of cousins in Mahabarata. It happened because of tri incidents, which are power struggle, envy, and incitement of Sengkuni. The goal in this Research is to analyze the incident of Bharatayuddha war, in Mahabarata story. Basically this story has already occured in Indonesia, as we can see and analyze from the conflicts that happened in the country.Conflict is the root of a war that spilled lots of blood. This very conflict had also happened in Indonesia, which is the fight between the people in the country. The essence of Indonesia is being an independent nation filled with diversity in unity, which is built upon the hopes and determination of our ancestors and the nation heroes to create the big nation. The unity of the entire country is absolutely priceless. It is a heritage, a gift from our ancestors who had fought with their lives for unity and independence.